THE PRACTICES AND CHALLENGES OF TEACHING ENGLISH TO YOUNG LEARNERS AT PRIMARY SCHOOLS IN BANDUNG - SLAMET SUWANTO, - (2018)
Since the Indonesian National Curriculum 2013 of primary school Indonesia does not include English as a compulsory subject, unlike the previous one, the teaching of English to young learners varies from one school to another. This study aims to investigate the practices and challenges of teaching English to young learners (TEYL) at primary schools in Bandung city. The research adopted multiple case study research design. Data were collected from survey, questionnaires, interviews, observation, and document analysis. The survey was distributed randomly to 30 teachers from 30 different schools based on the territory. Four teachers from four different schools were selected to participate in the questionnaires and in the investigation of TEYL implementation ant its challenges at schools. The data were triangulated and analysed descriptively to examine the practices and challenges of TEYL in primary schools. (Creswell, 1994). The findings revealed a discrepancy between the government policy and the actualization of English teaching at primary schools. The implementation of TEYL at primary schools takes various forms, some schools conducted English as a local content and some conducted English as an extracurricular. Of the 30 investigated schools, 21 (70%) schools conducted English as a local content, 7 (23%) schools conducted English as an extracurricular, and only 2 (7%) schools did not conduct English in their teaching learning process. In terms of planning, process, and evaluation of TEYL at schools, due to the absence of government supervision, teachers have their own authorities to design the curriculums in their schools. Interviews reveal many challenges in implementing TEYL due to different teachers' competencies, school facilities, English environment and exposure. The study also provides some suggestions on some possible best implementation for TEYL at primary schools such as government policy towards English teaching at primary schools, teachers' training, English teachers' community and English environment. ----Kurikulum 2013 sekolah dasar tidak memasukkan bahasa Inggris sebagai mata pelajaran wajib maupun muatan local dalam struktur kurikulumnya. Tidak seperti kurikulum sebelumnya yang mencantumkan bahasa Inggris sebagai muatan local, pengajaran bahasa Inggris untuk anak di Indonesia sangat bervariasi dari sekolah yang satu dengan sekolah yang lain. Penelitian ini dilakukan untuk menginvestigasi praktek pengajaran bahasa Inggris anak di sekolah dasar se kota Bandung beserta tantangan dalam implementasainya di lapangan. Penelitian ini menggunakan metode multiple case study. Teknik pengumpulan data menggunakan survei, questioner, wawancara, observasi, dan analisis dokumen. Survei dan questioner diberikan kepada 30 guru bahasa Inggris di semua wilayah di kota Bandung. Dari 30 guru yang diinvestigasi, terpilih empat sekolah dan empat guru bahasa Inggrris untuk diteliti lebih dalam implementasi pengajaran bahasa Inggris di sekolah. Data yang terkumpul dianalisis dan dideskripsikan untuk menggambarkan praktek pengajaran bahasa Inggris dan tantangan yang dihadapi di sekolah dasar. Temuaan di lapangan menunjukkan ketidaksesuaian antara kebijakan pemerintah tentang status bahasa Inggris di sekolah dan kenyatan di lapangan. Dai 30 sekolah yang diinvestigasi, 21 sekolah (70%) menyelenggarakan bahasa Inggris sebagai mutan local, 7 sekolah (23%) sebagai ekstra kurikuler, dan 2 sekolah (7%) tidak menyelenggarakan pengajaran bahasa Inggris di sekolah. Dalam hal perencanaan, implementasi, dan evaluasi, karena ketiadaan pengawasan dari pemerintah, maka ketiga hal tersebut berbeda dari sekolah yang satu dengan sekolah yang lain. Setelah mewawancarai beberapa guru, muncul banyak kendala dalam implementasi pengajaran bahasa Inggris di sekolah dasar diantaranya kebijakan pemerintah, kemampuan bahasa Inggris guru, dan lingkungan bahasa Inggris yang tidak mendukung. Penelitian ini juga memberikan rekomendasi yang bisa dilakukan sekolah terhadap implementasi pengajaran bahasa Inggris seperti pengakuan status guru bahasa Inggris SD oleh pemerintah, pelatihan pengajaran bahasa Inggris untuk anak, pembentukan komunitas guru bahasa Inggris untuk anak, dan pengadaan lingkungan yang mendukung pengajaran bahasa Inggris anak di sekolah dasar.